Chemical constituents from Ficus natalensis hochst (Moraceae) and their chemophenetic significance. (April 2021) - Mbougnia, Judith F.T.; Happi, Gervais M.; Bitchagno, Gabin T.M.; Awouafack, Maurice D.; Lenta, Bruno N.; Kouam, Simeon F.; Tane, Pierre; Sewald, Norbert; Tene, Mathieu
Abstract: Phytochemical investigation of the stem bark of Ficus natalensis afforded eleven compounds including one ceramide (1 ), two anthraquinones (2, 3 ), four triterpenes (4 –7 ), two polyols (8, 9 ) and two steroids (10, 11 ). The structures of the compounds were determined by spectroscopic analyses including IR, UV, MS, 1D- and 2D- NMR ( 1 H, 13 C, 1 H– 1 H COSY, HMQC, HMBC and NOESY), as well as by comparison with literature data. The antibacterial activity and the cytotoxicity of the extract, fractions and some isolated compounds (3, 5, 8 and 9 ) were evaluated. Some fractions and sub-fractions from various column chromatography displayed moderate antibacterial activity with diameter zone of inhibition (DZI) ranging from 7 to 10 mm. None of the compounds tested had activity. In the present study, all the compounds are isolated for the first time from the species F. natalensis . Compounds 2, 4 –7, 10 and 11 were previously reported from the genus Ficus . The chemophenetic significance of the isolated compounds is discussed. Graphical abstract: Image 1 Highlights: This is the first report of secondary metabolites from Ficus natalensis . The chemophenetic significance of the isolated compounds is discussed. Ceramides, anthraquinones, triterpenes and sterols might serve as chemotaxonomic markers for the genus Ficus .